Association between split shift work and work-related injury and disease absence - Ko, Kwon; Park, Jae Bum; Lee, Kyung-Jong; Jeong, Inchul (Annals of occupational and environmental medicine, 2021)
Shift work (particularly split shifts) has been noted among the working conditions that hinder sustainable work. However, little is known regarding the effects of split shifts on health. This study aimed to investigate the association between split shift work and work-related injury and disease absence. This study used data from the fifth Korean Working Conditions Survey and included 4,042 paid shift workers. Shift work type and self-reported work-related injury and disease absence were investigated using a questionnaire. Logistic regression analysis was performed to investigate the association between split shift work and work-related absence with rotating shift worker as the reference group. Of the 4,042 shift workers, 980 (24.3%) were split shift workers. The adjusted odds ratio (aOR) of split shift for absence due to work-related injury was high at 2.94 (95% confidence interval [CI]: 1.85-4.68) and the aOR of split shift for absence due to work-related disease was also high at 1.58 (95% CI: 1.09-2.29) compared to rotating shift. Split shift work leads to an increased risk of absences due to work-related injury and disease.